IMPLEMENTATION AND REMEDIAL PROBLEMS IN BIOLOGY LEARNING - Silvana Syahraini; Salwa Rezeqi (Jurnal Pelita Pendidikan, 2021)
Remedial learning is given to students through two main stages: the diagnosis of learning difficulties and remedial treatment. All remedial learning must end with a retest. The main stage of remedial learning is often overlooked in the implementation of remedial learning in schools. This study aims to determine the understanding, implementation, and problems of remedial learning in biology subjects in odd semester students of Class XI MIPA SMA. This research is descriptive qualitative research using data analysis techniques Miles and Huberman's model. The instruments used were questionnaires and interviews. The results showed that the teacher's understanding of remedial learning could be categorized as good. The implementation of remedial is in the very good category, except for the time for implementing remedial learning, which is in the category of less suitable remedial technical guidelines. The category of remedial learning problems in biology subjects is insufficient. However, the interview results showed a lack of time planning by schools related to remedial implementation at the end of each basic competency. Remedial learning in biology subjects in class XI SMA needs to pay attention to the time aspect in the implementation and planning of learning by schools and teachers.